(untitled) (JBN (Jurnal Bedah Nasional), 2025)
Aim: The aim of this case report was to study the importance of comprehensive examinations of synchronous cancer to avoid repeated surgeries and improved the outcome. Case Presentation: a 77-years-old man with sigmoid adenocarcinoma and ascending colon mass was suspected to be a synchronous tumor. The patient complained difficulty in defecation accompanied with weight loss and change of bowel habit, especially hardened and bloody stool. Abdominal CT-scan showed thickened irregular diffuse along the ascending colon to caecum and colonoscopy found circular mass, 30-35cm from the anal verge. The extended right hemicolectomy and anterior resection were performed. There were no notable issues, hence we performed ileal colon and colorectal anastomoses. Pathological result for both specimens were adenocarcinoma. Patient was uneventful and discharged 4 days after the surgery. Conclusion: Synchronous CRC was an independent prognostic factor associated with poor overal survival and disease free survival. The primary treatment of synchronous colorectal cancer is surgical resection. Simultaneous right colectomy and anterior resection can be considered for synchronous colorectal malignancies to avoid repeated surgeries, ensuring a similar or potentially improved outcome.